Life satisfaction and social trust as a component of social capital among students in the Zachodniopomorskie Region - Będzik, Beata; Gołąb, Sylwia (Satysfakcja z życia i zaufanie społeczne jako komponent kapitału społecznego wśród zachodniopomorskich studentów, 2020)
The article is part of the search for new generators of socio-economic development. The goal was to assess social trust (generalized, trust in public institutions) among students as current and future creators and disposers of this resource, and to verify the relationship between life satisfaction and trust in order to search for mechanisms to create it. The study was conducted in 2020 using the SWLS questionnaire extended with questions about social capital. The analyses were supplemented with statistics based on ESS data. The results confirmed the positive relationship between life satisfaction and trust, although its strength was determined by the dimension of trust which was positively correlated with the belief that the commune authorities supported social initiatives and the possibilities of influencing the functioning of the commune
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 10, s. 5-17